2016
DOI: 10.1111/maec.12350
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic diversity and structure of a dominant tropical seagrass, Cymodocea rotundata, in the Western Pacific region

Abstract: Cymodocea rotundata is an ecologically important tropical pioneer seagrass species distributed in the Indo-Pacific region. The population genetic diversity and structure of this species were analysed at 46 sites spanning the Philippines, Ryukyu Islands (northern limit) and Hainan Island, by using microsatellite simple sequence repeat (SSR) markers. Analyses revealed the persistence of C. rotundata likely relies on local population dynamics and fitness influenced by environmental gradients, with sexual reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Though not explicitly examining population dynamics across this central‐peripheral junction, a microsatellite analysis of a seastar ( Acanthaster planci ) showed no differentiation between a site in the central Philippines and the Ryukyu Islands and no decrease in genetic diversity (Yasuda et al., ). Microsatellite analyses of three species of seagrass ( Cymodocea serrulata, Cymodocea rotunda, and Enhalus acoroides ) indicate that recruitment to the Ryukyus occurs from the northeastern Philippines (Arriesgado et al, ; Nakajima et al, ). Reduced genetic diversity was only found in Ryukyu Island populations of E. acoroides and C. serrulata , however, providing further evidence that many tropical taxa may not experience measurable edge effects in peripheral populations within the Kuroshio Current.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though not explicitly examining population dynamics across this central‐peripheral junction, a microsatellite analysis of a seastar ( Acanthaster planci ) showed no differentiation between a site in the central Philippines and the Ryukyu Islands and no decrease in genetic diversity (Yasuda et al., ). Microsatellite analyses of three species of seagrass ( Cymodocea serrulata, Cymodocea rotunda, and Enhalus acoroides ) indicate that recruitment to the Ryukyus occurs from the northeastern Philippines (Arriesgado et al, ; Nakajima et al, ). Reduced genetic diversity was only found in Ryukyu Island populations of E. acoroides and C. serrulata , however, providing further evidence that many tropical taxa may not experience measurable edge effects in peripheral populations within the Kuroshio Current.…”
Section: Discussionmentioning
confidence: 99%
“…The NEC bifurcation occurs between the latitudes of 11°-16.5°N (Qiu & Lukas, 1996) (Arriesgado et al, 2015(Arriesgado et al, , 2016Nakajima et al, 2014).…”
Section: Genetic Differentiation Within the Kuroshio Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the genetic diversity, clonality and connectivity of seagrasses globally is highly context dependent (Jover et al 2003;Olsen et al 2004;Procaccini et al 2007;Sinclair et al 2014;Arriesgado et al 2016;Kendrick et al 2016;Hernawan et al 2017;Putra et al 2018), with some studies reporting high genetic diversity and population structuring at regional and local scales (Diekmann et al 2005;van Dijk & van Tussenbroek 2010;Becheler et al 2010;Sherman et al 2016), emphasizing the role of near and off-shore currents (Muñiz-Salazar et al 2005;Nakajima et al 2014). Conversely, in a few cases, low levels of genetic diversity and shared genotypes, even across exceptionally large spatial scales, have been recorded (van Dijk & van Tussenbroek 2010;Evans et al 2014;Nakajima et al 2014;Phan et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite (SSR: simple sequence repeat) markers for polymorphism analysis are known to be effective for analyzing the reproductive mechanisms of many organisms. Nuclear SSR markers with high polymorphism might also contribute to the analysis of parenthood, kinship, genetic structure, and population genetics [ 8 , 9 , 10 , 11 , 12 , 13 ]. Nagano prefecture is one of the most productive areas for matsutake mushroom growth and has recently had the highest annual yield of this product in Japan (Forestry Agency, Ministry of Agriculture, Forestry and Fisheries: Japan Annual report on trends in forest and forestry in Japan, Fiscal year 2009 (Summary)).…”
Section: Introductionmentioning
confidence: 99%